Twitter and Political Campaigning. Issue 9 (September 2015) - Vergeer, Maurice
Abstract The use of Twitter by politicians, parties, and the general audience in politics, particularly during election campaigns, has become an extremely popular research field almost overnight. Even though Twitter, a medium that emerged early in 2006 – the first tweet was posted on 21 March 2006 by Jack Dorsey, co‐founder of Twitter – and elections occurring only every few years, it has already received much academic attention. The studies produced are very diverse, ranging from analyzing how politicians or citizens use Twitter, to looking at their activities and the content of political Twitter messages, to network studies of Twitter users. This review will cover many types of studies that characterize the field. The large diversity in the studies conducted on elections will be represented in this review of approaches.